2017
DOI: 10.1097/rli.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Gadobutrol in Renally Impaired Patients

Abstract: ObjectiveThe aim of this study was to assess the potential risk of gadobutrol-enhanced magnetic resonance imaging (MRI) in patients with moderate to severe renal impairment for the development of nephrogenic systemic fibrosis (NSF).Materials and MethodsWe performed a prospective, international, multicenter, open-label study in 55 centers. Patients with moderate to severe renal impairment scheduled for any gadobutrol-enhanced MRI were included. All patients received a single intravenous bolus injection of gadob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Moreover, MRI scanner accessibility and radiology expertise may influence the broad adoption of screening MRI to replace ultrasound. Finally, we did not evaluate potential safety issues related to repeated administration of GBCA for HCC surveillance, although recent studies have shown the safety of macrocyclic agents even in patients with impaired renal function . While further research is needed to ascertain any adverse effect of macrocyclic GBCA, HCC screening remains a high priority for cirrhosis patients, as HCC is the leading cause of death among cirrhosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MRI scanner accessibility and radiology expertise may influence the broad adoption of screening MRI to replace ultrasound. Finally, we did not evaluate potential safety issues related to repeated administration of GBCA for HCC surveillance, although recent studies have shown the safety of macrocyclic agents even in patients with impaired renal function . While further research is needed to ascertain any adverse effect of macrocyclic GBCA, HCC screening remains a high priority for cirrhosis patients, as HCC is the leading cause of death among cirrhosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not evaluate potential safety issues related to repeated administration of GBCA for HCC surveillance, although recent studies have shown the safety of macrocyclic agents even in patients with impaired renal function. 44 While further research is needed to ascertain any adverse effect of macrocyclic GBCA, HCC screening remains a high priority for cirrhosis patients, as HCC is the leading cause of death among cirrhosis patients. Meanwhile, trials assessing the potential feasibility of annual noncontrast MRI in comparison with traditional ultrasound screening are currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in practice patterns, such as routine screening for renal insufficiency, withholding GBCAs in patients in advanced CKD, and a widespread shift away from the high‐risk GBCAs (ie, gadopentetate [Magnevist], gadodiamide [Omniscan], and gadoversetamide [OptiMARK]) have almost completely eliminated new cases of NSF. At least six prospective trials involving more than 2200 patients have been conducted to assess the risk of NSF in patients with renal impairment receiving GBCAs . Nearly half of the patients in these trials had eGFRs <30 mL/min/1.73‐m 2 , and one study included 268 patients on dialysis .…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
“…At least six prospective trials involving more than 2200 patients have been conducted to assess the risk of NSF in patients with renal impairment receiving GBCAs. 21,[89][90][91][92][93] Nearly half of the patients in these trials had eGFRs <30 mL/min/1.73m 2 , and one study included 268 patients on dialysis. 89 These studies tested all GBCAs except the three agents (ie, the high-risk agents listed above) with the strongest associations with NSF.…”
Section: Updates On Epidemiologymentioning
confidence: 99%
“…The administration of contrast in patients with severely impaired renal function is controversial due to the risk of nephrogenic systemic fibrosis, 78 however, new insights suggest that modern macrocyclic GBCAs may not be associated with the development of nephrogenic systemic fibrosis even when administered to high risk chronic kidney disease patients. [79][80][81][82] Renal T 2 mapping has thus far only been evaluated in mouse models, which showed that renal cortex T 2 values increase after kidney transplantation 73 and that renal T 2 is highly correlated with the histological cystic index in a polycystic kidney disease model. 83 Further research is needed to assess whether T 2 mapping could be useful for assessment of edema, or for the prediction of cyst progression in humans.…”
Section: Kidneymentioning
confidence: 99%